In-Service Training and Support for Teachers to Prepare for the Creative Economic Zone in Singosari - Emaliana, Ive; Wardhani, Ni Wayan Surya; Sugiarto, Yusron; Hikmiah, Ziadatul - (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
Ideally, teachers should be able to publish the results of classroom action research as a reflection of teacher professional competence as well as an evaluation of teaching practices. Therefore, systematic and sustainable training and mentoring programs are needed to allow them to maximize their potential. This community service program aims to provide solutions to these problems through policy recommendations through the initiation of the 'Teacher Writing' task force. This initiative is projected to be a systematic and sustainable program that allows teachers to maximize their professional competence as dictated in one of the 4 pillars of teacher competence set by the government. This program was conducted for teachers in Malang Regency, especially Singosari, with consideration that recently Singosari was declared as a Creative Economic Zone (KEK).